Positron Emission Tomography Imaging of Macrophages in Atherosclerosis with F-18-GE-180, a Radiotracer for Translocator Protein (TSPO) - Sanna Hellberg; Heidi Liljenbäck; Olli Eskola; Veronique Morisson-Iveson; Matthew Morrison; William Trigg; Pekka Saukko; Seppo Ylä-Herttuala; Juhani Knuuti; Antti Saraste; Anne Roivainen (WILEY-HINDAWI, 2022)
Intraplaque inflammation plays an important role in the progression of atherosclerosis.) The 18 kDa translocator protein (TSPO) expression is upregulated in activated macrophages, representing a potential target to identify inflamed atherosclerotic plaques. We preclinically evaluated F-18-GE-180, a novel third-generation TSPO radioligand, in a mouse model of atherosclerosis.
Methods. Nine hypercholesterolemic mice deficient in low density lipoprotein receptor and apolipoprotein B48 (LDLR(-/-)ApoB(100/100)) and six healthy C57BL/6N mice were injected with 10 MBq of F-18-GE-180. Specificity of binding was demonstrated in three LDLR(-/-)ApoB(100/100) mice by injection of nonradioactive reference compound of F-18-GE-180 before F-18-GE-180. Dynamic 30-minute PET was performed followed by contrast-enhanced CT, and the mice were sacrificed at 60 minutes after injection. Tissue samples were obtained for ex vivo biodistribution measurements, and aortas were cut into serial cryosections for digital autoradiography. The presence of macrophages and TSPO was studied by immunohistochemistry. The F-18-GE-180 retention in plaque areas with different macrophage densities and lesion-free vessel wall were compared.
Results. The LDLR-/-ApoB(100/100) mice showed large, inflamed plaques in the aorta. Autoradiography revealed significantly higher 18F-GE-180 retention in macrophage-rich plaque areas than in noninflamed areas (count densities 150 +/- 45 PSL/mm(2) versus 51 +/- 12 PSL/mm2, p < 0.001). Prominent retention in the vessel wall without plaque was also observed (220 +/- 41 PSL/mm(2)). Blocking with nonradioactive GE-180 diminished the difference in count densities between macrophage-rich and noninflamed areas in atherosclerotic plaques and lowered the count density in vessel wall without plaque.
Conclusion. F-18-GE-180 shows specific uptake in macrophage-rich areas of atherosclerotic plaques in mice. However, retention in atherosclerotic lesions does not exceed that in lesion-free vessel wall. The third-generation TSPO radioligand F-18-GE-180 did not show improved characteristics for imaging atherosclerotic plaque inflammation compared to previously studied TSPO-targeting tracers.